The influence of ontogenetic dietary fluctuations on zebrafish size and swimming performance - Marks, Chris; Lombardo, Steven M.; Formanik, Kristie L.; Moore, Francisco B.; Bagatto, Brian (Frontiers in Physiology, 2012)
Phenotypic flexibility is critical in determining fitness. As conditions change during ontogeny, continued responsiveness is necessary to meet the demands of the environment. Studies have shown that subsequent ontogenetic periods of development can interact with one another and shape developmental outcomes. The role genetic variation within populations plays in shaping these outcomes remains unclear. Four full-sub families of zebrafish Danio rerio were raised under for dietary regimes: high food rations for 60 days (HH), low food rations for 60 days (LL), high food rations for 30 days followed by low food rations for 30 (HL), and low food rations for 30 days followed by high food rations for 30 (LH). While diet significantly altered size at 30 days (high vs. low food rations), subsequent dietary change resulted equal sizes across all four feeding treatments. Swimming performance showed variation due to interactions between dietary treatments. Furthermore, there was significant family level variation in the manner in which swimming performance responded to fluctuating dietary conditions. These results suggest that plastic responsiveness to subsequent environmental changes can be trait specific and vary significantly within populations.